2006
DOI: 10.1111/j.1600-0404.2005.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled study of oxcarbazepine in painful diabetic neuropathy

Abstract: In this study, no statistically significant difference in therapeutic effect was observed between oxcarbazepine (1200 mg/day) and placebo. However, further studies are necessary to assess the effective dose range of oxcarbazepine in the treatment of painful diabetic neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 7 publications
0
34
1
4
Order By: Relevance
“…18 -20 Two studies showed no benefit, 18,20 but a third showed a moderate benefit-17% more patients on oxcarbazepine had a Ͼ50% pain reduction compared to placebo, with an NNT of 6.023. 19 The study showing a positive response had a slightly higher completion rate (73% 19 compared to 67%).…”
Section: Analysis Of Evidence In Patients With Pdnmentioning
confidence: 99%
“…18 -20 Two studies showed no benefit, 18,20 but a third showed a moderate benefit-17% more patients on oxcarbazepine had a Ͼ50% pain reduction compared to placebo, with an NNT of 6.023. 19 The study showing a positive response had a slightly higher completion rate (73% 19 compared to 67%).…”
Section: Analysis Of Evidence In Patients With Pdnmentioning
confidence: 99%
“…These agents, which include topiramate (14 -16), lamotrigine (17), oxcarbazepine (18,19), and gabapentin (20 -22) have shown varying efficacy in clinical trials.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…[44] Okskarbazepin, sodyum kanal blokajı yaparak analjezik etki gösterir; trigeminal nevralji, diyabetik polinöro-pati, radikülopati ve postherpetik nevraljide etkin olduğunu gösteren çalışmalar mevcuttur. [45][46][47] Nöropatik ağrı tedavisinde, 150 mg/gün dozuyla başlanarak, üç gün aralarla 150 mg'lık doz artışları yapılarak, maksimum 1800 mg/gün dozuna kadar çıkılır. Okskarbazepin, karaciğerde metabolize olur; başlıca yan etkileri arasında, dizziness, bulantı, baş dönmesi, bulanık görme ve ataksi bulunur.…”
Section: Anti̇epi̇lepti̇klerunclassified